2015
DOI: 10.5614/j.math.fund.sci.2015.47.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Study on Heat Island Effect Induced by Land Use Change Increased Temperature in Metropolitan

Abstract: Abstract. The heat island (HI) effect in metropolitan Jakarta was studied using air temperature measurements at 9 meteorological stations in Jakarta, Tanjung Priok, Serang, Halim, Cengkareng, Pondok Betung, Curug, Bogor, Citeko during 1986-2008 and Serpong during 2008-2011 and 2013 land use for forest, industry, water, settlement, open/cleared land in 1997, 2004, 2012; and total number of industries and total number of vehicles during 1986-2011. Harmonic analysis was used to remove the seasonal component fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The environmental ramifications of the COVID-19 pandemic have been manifested in various facets, notably in alterations to the climate. Diminished human endeavors, encompassing urbanization, transportation, industry, and settlement, have been linked to temperature declines [30,31]. Investigations into the LST prior to and amid the Covid-19 pandemic in regions such as Wuhan City, China [32], Istanbul, Turkey [33], and India [34]have indicated that, during the enforcement of lockdown policies, the average LST was observed to be lower than the periods preceding or following the lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental ramifications of the COVID-19 pandemic have been manifested in various facets, notably in alterations to the climate. Diminished human endeavors, encompassing urbanization, transportation, industry, and settlement, have been linked to temperature declines [30,31]. Investigations into the LST prior to and amid the Covid-19 pandemic in regions such as Wuhan City, China [32], Istanbul, Turkey [33], and India [34]have indicated that, during the enforcement of lockdown policies, the average LST was observed to be lower than the periods preceding or following the lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…The inhabitants need land for their daily activity i.e. housing, office, industry, and commercial, trigger the land-use/land-cover change and urban sprawling [Firman, 1997;Lestari et al, 2015]. Land-use/landcover change and urban sprawling would be impacted to the quality of environment for example urban heat island, environmental pollution (atmospheric, water, soil), flooding [Wibowo & Rustanto, 2013;Costa, et al, 2016;Heald & Geddes, 2016;Murakami et al, 2017;Sutjiningsih, 2017;Effendi et al, 2018];.…”
Section: Ramadhani Yanidar Faculty Of Landscape Architecture and Envimentioning
confidence: 99%
“…Researchers have stated that UHI is related to Jakarta's Open Green Space (OGS) degradation [5,6]. Many OGS and other natural features of the land in Jakarta have been converted into buildings in the past 30 years [7,8].…”
Section: Introductionmentioning
confidence: 99%